2014
DOI: 10.1111/php.12368
|View full text |Cite
|
Sign up to set email alerts
|

Oxidatively Generated Damage to Cellular DNA by UVB and UVA Radiation,

Abstract: This review article focuses on a critical survey of the main available information on the UVB and UVA oxidative reactions to cellular DNA as the result of direct interactions of UV photons, photosensitized pathways and biochemical responses including inflammation and bystander effects. UVA radiation appears to be much more efficient than UVB in inducing oxidatively generated damage to the bases and 2-deoxyribose moieties of DNA in isolated cells and skin. The UVA-induced generation of 8-oxo-7,8-dihydroguanine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
233
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(237 citation statements)
references
References 217 publications
(313 reference statements)
3
233
0
1
Order By: Relevance
“…9,10,46,47 UVA wavelengths were used in this experiment because they represent 75% of the terrestrial UV radiations, they are known to reach the corneal endothelium, and they efficiently induce ROS. [6][7][8]48 H 2 O 2 , an oxidizing component induced by the mitochondrial respiratory chain, was also used to assess sensitivity to oxidative stress. Both UVA-and H 2 O 2 -induced cell death methods showed that FECD and healthy cultured cells behave similarly in the presence of oxidative stress (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10,46,47 UVA wavelengths were used in this experiment because they represent 75% of the terrestrial UV radiations, they are known to reach the corneal endothelium, and they efficiently induce ROS. [6][7][8]48 H 2 O 2 , an oxidizing component induced by the mitochondrial respiratory chain, was also used to assess sensitivity to oxidative stress. Both UVA-and H 2 O 2 -induced cell death methods showed that FECD and healthy cultured cells behave similarly in the presence of oxidative stress (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…8 Together, the high aerobic metabolism, the lifetime exposure to toxic sunlight, and the fact that the corneal endothelial cells in vivo are arrested in the G 1 phase of the cycle (i.e., nonmitotic cells) make the corneal endothelium prone to oxidative stress. recently described in FECD corneal endothelial cells, mostly at the level of mitochondrial DNA (mtDNA).…”
mentioning
confidence: 99%
“…The effects caused by exposure to ultraviolet (UV; 280-400 nm) radiation are well documented in the literature [1,2]; however, the effects of visible (VIS; 400-760 nm) and near-infrared (NIR; 760-3,000 nm) radiations have not yet been fully elucidated, and recent studies have evaluated their effects on the skin [3,4,5]. It is well known that moderate sun exposure is essential for the vitamin D synthesis that is fundamental for the bone and muscle status [6].…”
Section: Introductionmentioning
confidence: 97%
“…8). Oxidation of DNA by ROS gives rise to several types of lesions, the most common of which is 8-oxo-7,8-dihydroguanine (8-oxoGua) [22]. Crosslinks between DNA and proteins also arise from the generation of aldehydes from the oxidation of lipids [23].…”
Section: Uvr Effects At the Molecular Levelmentioning
confidence: 99%